Predicting middle-distance track and cross-country performances of national and international level adolescent runners - Bliss, A.; Waldron, M.; Maxwell, N. (European Journal of Sport Science, 2022)
This study evaluated the contribution of physiological data collected during laboratory testing in predicting race performances of trained junior middle-distance track (TK) and cross-country (XC) athletes. Participants performed a submaximal incremental ramp test, followed by an incremental test to exhaustion in a laboratory, with the results used to predict either 800 m TK, 1500 m TK or 4000-6000 m XC race performance. Twenty-eight participants (male (M), 15; female (F), 13) were analysed (age = 17 ± 2 years, height = 1.72 ± 0.08 m, body mass = 58.9 ± 8.9 kg). Performance times (min:s) for 800 m were: M, 1:56.55 ± 0:05.55 and F, 2:14.21 ± 0:03.89; 1500 m: M, 3:51.98 ± 0:07.35 and F 4:36.71 ± 0:16.58; XC: M (4900 ± 741 m), 16:00 ± 01:53; F (4628 ± 670 m), 17:41 ± 02:09. Stepwise regression analysis indicated significant contributions of speed at VO2max (VO2max), and heart rate maximum (HRmax) to the prediction of 800 m TK (F(2,15) = 22.51, p < 0.001, adjusted R 2 = 0.72), VO2max for 1500 m TK (F(1,13) = 36.65, p < 0.001, adjusted R 2 = 0.72) and VO2max, allometrically scaled to body mass and speed at lactate threshold (sLT) for XC (F(2,17) = 25.1, p < 0.001, adjusted R 2 = 0.72). Laboratory-based physiological measures can explain 72% of the variance in junior TK and XC events, although factors that explain performance alter depending on the race distance and tactics. The factors determining performance in TK and XC events are not interchangeable.